“Dando forma, vida e cor”: a pintura de paisagens e a construção da identidade cultural no Recife (1922-1932) - MELO, Paulo Henrique Rodrigues (2010)
The current research has by its purpose "to read" the pictorial production of Pernambuco in the decade of 20 (1922 - 1932) and understand how its possible meanings and elements were interpreted, manipulated and appreciated in the constructions produced by the painters in the point of local/national cultural identity. Among a variety of gender that passes by portait paintings until the historic painting, we are going to linger at landscape painting, because this one is repitedly understood and used in those formulations as inherent to the identity and the individual history of Pernambuco. In the core of those formulations, we are going to find the conflict between modern and traditional, making evident the tensions brought by the modernizing speech that contaminated the Recife's men imaginary inte the 20th years, carring artists and intellectual people to have an attitude against it or in the favour. This case can be observated in those who connected direct or indirectly to the regional traditionalist movement which will detain more attention. We will understand the work of art as a social practice that built itself in the precisely continuation of historicity in the plastic form and in within social, that its product is introduced. We will approach to the explained model built by the french sociologist Pierre Bourdieu, whose fundamental terms are the Campo and the Habitus. We prioritize the intersection of visual and written sources, taking into consideration that eachone has its way of being and in the same time maintain complex relationshipswith each other through a reciprocal operation by introducing a way to see and say about the reality producing meanings and senses.